Frequency and phase correction of J‐difference edited MR spectra using deep learning. Issue 4 (18th November 2020) - Tapper, Sofie; Mikkelsen, Mark; Dewey, Blake E.; Zöllner, Helge J.; Hui, Steve C. N.; Oeltzschner, Georg; Edden, Richard A. E.
Abstract : Purpose: To investigate whether a deep learning‐based (DL) approach can be used for frequency‐and‐phase correction (FPC) of MEGA‐edited MRS data. Methods: Two neural networks (1 for frequency, 1 for phase) consisting of fully connected layers were trained and validated using simulated MEGA‐edited MRS data. This DL‐FPC was subsequently tested and compared to a conventional approach (spectral registration [SR]) and to a model‐based SR implementation (mSR) using in vivo MEGA‐edited MRS datasets. Additional artificial offsets were added to these datasets to further investigate performance. Results: The validation showed that DL‐based FPC was capable of correcting within 0.03 Hz of frequency and 0.4°of phase offset for unseen simulated data. DL‐based FPC performed similarly to SR for the unmanipulated in vivo test datasets. When additional offsets were added to these datasets, the networks still performed well. However, although SR accurately corrected for smaller offsets, it often failed for larger offsets. The mSR algorithm performed well for larger offsets, which was because the model was generated from the in vivo datasets. In addition, the computation times were much shorter using DL‐based FPC or mSR compared to SR for heavily distorted spectra. Conclusion: These results represent a proof of principle for the use of DL for preprocessing MRS data.